Efektivitas Pelatihan Better Together dalam Meningkatkan Co-Parenting Ayah dan Ibu Saat Mengasuh Anak Usia 1-3 Tahun - Regina Nareswari Putri Pratiwi; Linda Primana; Rose Mini Agoes Salim (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
The parental consistency in parenting is very important, especially for toddlers or around the age of one to three years, because they need rules and limits for their autonomy or independence that they are pursuing in their developmental tasks. Therefore, co-parenting or the cooperation of fathers and mothers in Parenting children is needed, so that fathers and mothers have similarities in applying the rules and methods of Parenting, so that children can optimize their self-regulation and independence learning. This study aims to test the effectiveness of Better Together Training in improving co-parenting of fathers and mothers when caring for children aged one to three years. The method used in this study is Pre-Experimental One Group Pretest-Posttest Design, which involves one experimental group without a control group. The data in this study was collected in three different times, namely pre-test, post-test, and follow-up test using the Brief CoParenting Scale. Statistical analysis using ANOVA's Repeated Measures found that there was a significant increase in parents' co-parenting levels scores between different measurement times (i.e., pre-test, post-test, and follow-up test), F(2, 30) = 4.17, p <.025, ?2 p = .22. The evaluation of the implementation of this training also obtained positive results from the participants, which was considered very beneficial for them.